2007
DOI: 10.1111/j.1440-1797.2007.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic eosinophilic peritonitis in continuous ambulatory peritoneal dialysis: Experience with percutaneous catheter placement

Abstract: Idiopathic EP is infrequent among patients on CAPD following percutaneous catheter placement, but should be differentiated from infectious PD-related peritonitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Eosinophilic peritonitis has most often been described in patients initiating PD: incidence 4% – 60% (with more recent studies pointing to a lower incidence since the 1990s) (5,6,10). In these cases, PD effluent cultures were negative and the pathogenesis was thought to be either an allergic reaction to a component of the PD system (catheter, solutions, sterilants, or plasticizers) or due to the introduction of air into the peritoneum (5-10). In the majority of these cases, the episodes were self-limited and of little consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophilic peritonitis has most often been described in patients initiating PD: incidence 4% – 60% (with more recent studies pointing to a lower incidence since the 1990s) (5,6,10). In these cases, PD effluent cultures were negative and the pathogenesis was thought to be either an allergic reaction to a component of the PD system (catheter, solutions, sterilants, or plasticizers) or due to the introduction of air into the peritoneum (5-10). In the majority of these cases, the episodes were self-limited and of little consequence.…”
Section: Discussionmentioning
confidence: 99%
“…Identified risk factors associated with EP are exposure to vancomycin, infections (fungal or viral) after a recent catheter replacement or treatment with icodextrin, a polymer used to increase ultrafiltration in order to treat volume overload in ESRD [215,216]. More recent data from a prospective study of 48 patients undergoing CAPD suggested a smaller prevalence of PFE of less than 10% and shows no significant correlation between PBE and PFE [41]. PBE is typically detected in asymptomatic patients following catheter replacement and usually resolves spontaneously within a few days [41,213], although the course can be chronic or recurring with permanent changes in membrane function [217].…”
Section: Eosinophilia In Kidney Diseasementioning
confidence: 99%
“…More recent data from a prospective study of 48 patients undergoing CAPD suggested a smaller prevalence of PFE of less than 10% and shows no significant correlation between PBE and PFE [41]. PBE is typically detected in asymptomatic patients following catheter replacement and usually resolves spontaneously within a few days [41,213], although the course can be chronic or recurring with permanent changes in membrane function [217]. Considering the favorable prognosis, a steroid treatment in general is not recommended [214].…”
Section: Eosinophilia In Kidney Diseasementioning
confidence: 99%
“…PD is a treatment methodology that makes use of the semipermeable function of the peritoneum and is more biocompatible with body membranes. Thus, the elevation of EOC in PD patients is less common and milder than that in HD patients [12]. Accordingly, eosinophilia in PD patients is rare and not a common concern for clinicians and researchers.…”
Section: Introductionmentioning
confidence: 99%